System architecture of offshore oil production systems - Keller, James (James Thomas) (Massachusetts Institute of Technology, 2008)
Thesis (S.M.)--Massachusetts Institute of Technology, Dept. of Aeronautics and Astronautics, 2008. Includes bibliographical references (p. 117-118). This thesis presents an approach to applying Systems Architecture methods to the development of large, complex, commercial systems, particularly offshore oil and gas productions systems. The aim of this research was to assist BP in the development of concepts for a multi-billion dollar oil production system, particularly in the unprecedented deep water arctic locations prone to seismic activity, as well as in existing fields that must be extended. The thesis demonstrates that these systems can be decomposed and analyzed using rigorous, methodical system architecture thinking that archives and represents tacit knowledge in several graphical frameworks. The thesis breaks the architecture of oil and gas production systems into two problems. The first problem is the architecture of one facility and one reservoir; a classic problem of assigning function to form. The second problem is the architecture of multiple facilities and multiple reservoirs; a classic problem of connection and routing. For the first problem, the production process is decomposed using Object Process Methodology (OPM). The decompositions provide a methodology to capture industry knowledge that is not always explicitly stated and provides a framework to explore the entire architectural design space. The thesis then describes how these decompositions of general and specific oil systems can be used to develop software models, using the meta-language tool OPN (Object Process Network), that successfully generate thousands of architecture concepts. This set of feasible architectures can be prioritized and better understood using metrics in an effort to down-select to a handful of preferred concepts to be carried forward for more detailed study and eventual development. (cont.) The approach to the second problem demonstrates that even a modest set of facilities and reservoirs have a huge number of ...